1986
DOI: 10.1097/00006254-198610000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A Deletion Map of the Human Y Chromosome Based on DNA Hybridization

Abstract: The genomes of 27 individuals (19 XX males, two XX hermaphrodites, and six persons with microscopically detectable anomalies of the Y chromosome) were analyzed by hybridization for the presence or absence of 23 Y-specific DNA restriction fragments. Y-specific DNA was detected in 12 of the XX males and in all six individuals with microscopic anomalies. The results are consistent with each of these individuals carrying a single contiguous portion of the Y chromosome; that is, the results suggest a deletion map o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
165
0
4

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(177 citation statements)
references
References 29 publications
8
165
0
4
Order By: Relevance
“…He concluded that, if the gonadoblastoma locus exists, it is within the region defined by interval 4B-7 which extends from centromere to the distal end of long arm (Page, 1987;Vergnaud et al, 1986). Lukusa et al reported that except for a few cases among individuals with dysgenetic gonad, gonadoblastoma was not found in patients with a karyotype 45,X/46,X,Ynf (Lukusa et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that, if the gonadoblastoma locus exists, it is within the region defined by interval 4B-7 which extends from centromere to the distal end of long arm (Page, 1987;Vergnaud et al, 1986). Lukusa et al reported that except for a few cases among individuals with dysgenetic gonad, gonadoblastoma was not found in patients with a karyotype 45,X/46,X,Ynf (Lukusa et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The fragment was subcloned into the pUC18 vector digested with these 2 enzymes. The 49f probe was originally described by Vergnaud et al (1986) and a gift from Dr. J. Weissenbach.…”
Section: Methodsmentioning
confidence: 99%
“…et al, 1986). The remaining six probes were gifts from Dr. J. Weissenbach (probes 47z, 52d, 50f2, 12f3, and 49f; Vergnaud et al, 1986) and a gift from Dr. D. C. Page (probe pDP1007(ZFY); Page et al, 1987). Probe 50f2 detects five different loci (50f2A to 50f2E) on the Y chromosome (see Fig.…”
Section: Cytogenetic Studiesmentioning
confidence: 99%